GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 572933833 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 572933833 records from 12259 constituent datasets: 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 132 records from Benthic foraminifera abundance of Hole 82-563. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 58081 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 136 records from Range table from benthic foraminifers in ODP Hole 192-1184A. 42 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 50 records from Range table from benthic foraminifers in ODP Hole 174-1071F. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 2 records from Abundance of benthos infauna at station GIK23011-2. 190 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 61 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 1269 records from Benthic foraminifera distribution of sediment core ASV11-858-3 (ASV 858). 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 14 records from Occurrence of mammalia relicts at site Wolfskehlen. 38 records from Occurrence of mammalia relicts at site Kugelsteinhöhle II. 366 records from My naturesounds - nature observations with sound recordings. 28 records from Range table from planktonic foraminifers in ODP Hole 178-1096B. 123 records from Range table from benthic foraminifers in ODP Hole 139-855A. 228 records from Range table from planktonic foraminifers in ODP Hole 145-883B. 115 records from Range table from benthic foraminifers in ODP Hole 149-899B. 1 records from Dinoflagellate abundance of Hole 38-345. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 27 records from Planktic foraminifera abundance of Hole 51-417B. 47 records from ANDEEP3: SeaStars (Echinodermata, Asteroidea). 71 records from Range table from planktonic foraminifers in ODP Hole 144-876A. 18 records from Range table from benthic foraminifers in ODP Hole 144-871B. 628 records from hauterivian_echinoids_of_the_paris_basin. 75754 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 126 records from Schulwald Marksuhl. 570 records from Planktic foraminifera abundance of Hole 94-606. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 14122 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 27 records from Wiese hinter der Schule (Darmstadt). 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 156 records from Collection Tentakulita fossil SMF. 7402 records from Helgeland Museum, Lepidoptera. 23 records from Plasm bearing foraminifera counts from multinet M32/3_MSN958. 8 records from Microzooplankton abundance and biomass at station NBP97-03-07-8. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 162 records from Antarctic fish Gobionotothen gibberifrons. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 3628 records from Wildbook for Whale Sharks. 18 records from Spielwiese. 67 records from Total foraminifera counts from M35/1_MSN1056. 189 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE7. 4 records from Nannofossil abundance of Hole 8-75. 17 records from Coccoliths in sediment core PS1529-8. 27 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI229. 1233 records from Saproxylic Beetles of the Tatra Mts.. 735 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 408 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 60 records from Phytoplankton abundance in surface water in October 1996, Chimbote, Peru. 153 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 81 records from Range table from planktonic foraminifers in ODP Hole 171-1050A. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 3125 records from Alterra (NL) - Entomofauna inventory in edges of arable fields province of Groningen. 5415 records from BioGIS - Land snails - HUJ collections. 1661 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82 (Australian Antarctic Data Centre). 15 records from Occurrence of mammalia relicts at site le gisemnet de Fongabon. 238 records from Elaboración de fichas de 5 especies de lacertilios: PROY-NOM-059-ECOL-2000. 325 records from Planktic foraminifera abundance of Hole 9-83. 2244 records from Helmintos parásitos de peces del sureste de México. 72358 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1997) (AfrOBIS). 350 records from Foraminifera distribution of sediment core SDSE194. 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 773 records from Neckartalsüdhang (Horb). 123 records from 4. GEO-Tag in Eberbach. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-092BX. 111 records from Landesweite NABU-Vogelrallye. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 11 records from Occurrence of mammalia relicts at site Leeheim. 10 records from Occurrence of mammalia relicts at site Pekarna. 9 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 246 records from Range table from planktonic foraminifers in ODP Hole 171-1052A. 289 records from Range table from planktonic foraminifers in ODP Hole 182-1132B. 5 records from Xanthichthys greenei , a new species of triggerfish ( Balistidae ) from the Line Islands. 36 records from Dinoflagellate abundance of Hole 40-365. 173 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 22107 records from Collection Crustacea SMF. 29187 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 1256 records from Foraminifera abundance of Hole 64-481. 127 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 156 records from Range table from planktonic foraminifers in ODP Hole 155-932B. 33584 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 6611 records from Nijmegen Natural History Museum (NL) - Herbarium. 6425 records from Likona Invertebrates. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 27 records from Vögel. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 15 records from Beisetal bei Niederbeisheim. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 200 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE233. 862 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 1000 records from Colección Limnológica del Chocó. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 9741 records from Finnish Entomological Database: Hymenoptera. 1310 records from Distribución, abundancia y riqueza específica de la avifauna terrestre en la Isla Espíritu Santo, Baja California Sur, México. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 330 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 4240 records from Crustacea collection of National Museum of Nature and Science. 23 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 109392 records from Biological Records Centre - Cranefly (Diptera; Tipuloidea) records for Britain to 2007. 8 records from Planktic foraminifera abundance of Hole 94-611B. 1 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 10 records from Content of different diatom species in sediment core GIK23259-2. 13387 records from ELM paleontology. 104907 records from Entomology Division, Yale Peabody Museum. 211137 records from Limnodata. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 29 records from Range table from planktonic foraminifers in ODP Hole 173-1065A. 46325 records from University of Ghana - Ghana Herbarium. 7250 records from All Ireland Marsh Fritillary Database. 1364 records from Irish Collembola records. 3199 records from kpabg_cyano. 38 records from Was lebt in der Brutzwiese?. 1194 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-29. 396 records from Planktic foraminifera abundance of Hole 60-456. 735 records from Diversidad de coleópteros scarabaeoidea del estado de Puebla (I). 1826 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 130 records from Total foraminifera counts from M35/1_MSN1068. 128 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 62 records from Faunal assemblage of sediment core TR149-31. 167 records from Range table from benthic foraminifers in ODP Hole 198-1210B. 2244 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 68 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 742 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 1634 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 170 records from Total foraminifera counts of multinet M21/3_MSN687. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 5 records from Nannofossil abundance of Hole 3-22. 56 records from Range table from planktonic foraminifers in ODP Hole 145-884B. 135488 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 32 records from Töpinger Mischwald. 2 records from Abundance of benthos infauna at station PS1241-1. 165 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 25723 records from Irish National Badger Sett Database. 295987 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 707 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 1733 records from Demersal and pelagic species from the Patagonian shelf (OBIS South America, SOUTHERN OCEAN SUB-NODE). 1236 records from Insect Collection (CeStuBio). 394175 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 1 records from Herpetology. 339 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 616231 records from Hawk Migration Association of North America - HawkCount. 472 records from Algaterra Types. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 216 records from Planktic foraminifera counts of sediment core RC14-9. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 891 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core GIK12392-1. 1368 records from Distribution of planktic foraminifers of core Y71-06-12. 3304 records from Planktic foraminifera abundance of Hole 41-369A. 3387 records from Sand flies of Eastern Africa. 9 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 5524 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 242401 records from Vascular Plants, Field notes, Trondheim (TRH). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 12 records from Abundance of microplankton from bottle APRIL-2000-K1. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 371 records from Bannwald Burghauser Forst. 192 records from Phytoplankton abundance in surface water in March 1997, Pisco, Peru. 3 records from Observation of birds at station PS14/153 along 49° West. 24298 records from The Fish Database of Taiwan. 69168 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 542 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 50274 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 22 records from Kaltenkirchen Brache. 40 records from BUND Naturschutzzentrum St. Julian. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 244408 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 8385 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 264 records from Die Milbenfauna der Nordseeinsel Wangerooge. 18496 records from Biological Records Centre - Lacewings and allied insects records from Britain and Ireland to 1999. 2080 records from Naturalis National Natural History Museum (NL) – Coelenterata. 3 records from Sasanidus, a new generic name for Noemacheilus kermanshahensis Bănărescu & Nalbant, with discussion of Ilamnemacheilus and Schistura (Teleostei; Nemacheilidae). 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 9349 records from Harriet Irving Botanical Gardens (HIBG). 60 records from Steuer Ad., 1939. The fishery grounds near Alexandria. XVIII Sipunculoidea, Phoronidea, Brachiopoda, Enteropneusta and Acrania. Notes and Memoirs No. 30. Fouad I Institute of Hydrobioloy and Fisheries, Egypt. 5444 records from CSIRO, Fish Survey, Albatross Bay - Gulf of Capentaria, North Australia, 1986-1988. 6 records from Oberservation of birds at station PS14/146 along 49° West. 3554 records from BioGIS - Israeli Lepidopterists Society. 2904 records from CSIRO, Rachel Cruises, Shark Data, Arafura Sea, North Australia, 1984. 21159 records from UTEP Vertebrates. 11101 records from Royal Ontario Museum Fungarium (TRTC). 462 records from John Muir Trust - Knoydart Lichens, 1990. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 60 records from Shrews of Poland. 95 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1243-2. 258 records from BIRDRACE Raumpatrouille Oriolus. 36 records from Total foraminifera counts of multinet FCA97C_MSN1339. 9 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 81 records from Planktic foraminifera abundance of Hole 14-136. 201 records from Planktic foraminifera abundance of Hole 11-103. 4 records from Planktic foraminifera counts of multinet PS31/054. 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 24 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100590. 20 records from Planktic foraminifera abundance of Hole 19-185. 1155 records from Planktic foraminifera abundance of Hole 72-516A. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 288 records from Planktic foraminifera abundance of Hole 94-610A. 144 records from Range table from planktonic foraminifers in ODP Hole 159-962D. 93 records from Range table from planktonic foraminifers in ODP Hole 159-962B. 12 records from Range table from planktonic foraminifers in ODP Hole 175-1076C. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 32840 records from Lichen herbarium, Trondheim (TRH). 13750 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 897 records from Red list project inventory, vascular plants. 2 records from Nannofossil abundance of Hole 1-4. 2 records from Nannofossil abundance of Hole 6-50A. 7092 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 9281 records from Distribution of planktic foraminifers of core V30-40. 74 records from Planktic foraminifera abundance of Hole 62-465A. 517 records from Range table from benthic foraminifers in ODP Hole 143-865A. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1133A. 16 records from Nannofossil abundance of Hole 57-438. 4926 records from Universidad Autónoma de Madrid, Biología, Acalypha. 45 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE258. 22029 records from TNHC Ichthyology Collection. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais do Centro Universitário Univates (ZIUMCN-UNIVATES). 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 17532 records from BioFresh Pond Data. 1139 records from SWECO. 133 records from Total foraminifera counts of multinet M42/3_MSN1363. 1786 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V25-59. 68 records from Sandhofen. 176 records from Renaturierung Werse (Innenbereich Beckum). 156 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 389 records from Cephalaspidean Gastropods. 275 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 1994 records from Benthic foraminifera abundance of sediment core MD01-2416. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 11 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 111 records from Total foraminifera counts of multinet M12/3_MSN557. 3 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 10 records from Dinoflagellate abundance of Hole 81-552. 172 records from EEIKO Base de datos sobre plantas invasoras. 263 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - RISC Heteroptera Non-Native Species Records. 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 11 records from Microzooplankton abundance and biomass at station TT045_7-13. 9 records from Nannofossil abundance of Hole 66-490. 304 records from Planktic foraminifera counts of sediment core V29-173. 6 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 228 records from Phytoplankton abundance in surface water in June 1997, Pisco, Peru. 124 records from Total foraminifera counts of multinet M21/2_MSN650. 163 records from RSPB - Redshank nesting on saltmarshes in Britain (RSPB). 2790 records from SJRP - Herbário de São José do Rio Preto. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 26 records from Dinoflagellate abundance of Hole 81-554. 24 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 34 records from annex4. 6 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 27 records from Ostracoda abundance of Hole 42-376. 11 records from Pollen profile from sediment core AV14_K2-1. 80 records from Lahnufer in Villmar. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 96 records from Total foraminifera counts from multinet M31/2_MSN894. 46 records from Nannofossil abundance of Hole 94-611. 1547 records from Alterra (NL) - Entomofauna inventory in Speulder forest. 307 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 166 records from Foraminifera abundance of Hole 22-213. 3960 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 58946 records from Biological Records Centre - Isopoda (Interim dataset). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 229 records from Total foraminifera counts of multinet SO117_MSN1245. 161 records from Total foraminifera counts of multinet M26/1_MSN843. 94 records from Total foraminifera counts of multinet PO247/2_MSN1389. 329 records from Planktic foraminifera abundance of Hole 60-458. 7513 records from Bryophyte collection of Porto Herbarium (PO). 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 54 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 26 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 107916 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 60 records from Schulumgebung Grüterschule, Rheine. 48 records from Planktic foraminifera abundance of Hole 6-47. 1 records from Nannofossil abundance of Hole 94-611D. 46 records from Nannofossil abundance of Hole 26-254. 3769 records from Herbier de Wallis et Futuna. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_2-CTD20. 21 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 119 records from Kinorhyncha. 930 records from IITA Cameroon Insect. 6 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 171 records from Total foraminifera counts of multinet M21/2_MSN652. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 6 records from Microzooplankton abundance and biomass at station NBP97-08-31-7. 58 records from Nannofossil abundance in sediment core PS1295-5. 11826 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 64 records from Pilzlehrwald. 274 records from Bernhardsthal. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 75 records from Faunal assemblage of sediment core TR149-32. 1 records from Microplankton counts and carbon biomass at station TT008_4-TM3. 2 records from Nannofossil abundance of Hole 27-259. 110 records from (Table A.10) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (150-500 µm). 39 records from Ostracoda abundance of Hole 24-238. 24 records from Ostracoda abundance of Hole 42-371. 22 records from Nannofossil abundance of Hole 39-355. 3053 records from Guía ilustrada de los Staphylinidae (coleóptera) de México. 1344 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 1071 records from Pteridoflora de Morelos. 1033 records from Geochemistry and sedimentology on core PO200/10_8-2. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 34516 records from LSUMZ Mammals Collection. 78 records from Occurrence of mammalia relicts at site Einhornhöhle. 81684 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1992) (AfrOBIS). 66 records from (Table 9) Distribution of ostracode species in surface sediments of the southern Laptev Sea. 94 records from Plasm bearing foraminifera counts of multinet M21/2_MSN647. 136 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1371. 4 records from Nannofossil abundance of Hole 74-526B. 615 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 11 records from Coccoliths in sediment core PS1523-21. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 142 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 6 records from Planktic foraminifera abundance of Hole 4-24. 51 records from Planktic foraminifera abundance of Hole 18-177. 4732 records from Range table from planktonic foraminifers in ODP Hole 164-997A. 533 records from Range table from benthic foraminifers in ODP Hole 175-1076A. 8 records from Nannofossil abundance of Hole 5-34. 19 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 432 records from Foraminifera abundance of Hole 60-454. 29 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 1628 records from Agriculture and Agri-Food Canada, St. Johns, Newfoundland. 1797 records from Range table from benthic foraminifers in ODP Hole 149-898A. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 2015 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2495-3. 276 records from Planktic foraminifera abundance of Hole 11-102. 10 records from A new species of Probolomyrmex from Madagascar.. 716 records from Foraminifera distribution of sediment core Chain61-19. 75 records from Faunal assemblage of sediment core GS7603-9. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 561 records from EDIT - ATBI in Borjomi/Kharagauli (Georgia). 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 23 records from Alter Nördlicher Friedhof (München). 11 records from Waldgebiet Todtnau- Sonnhalde. 59 records from Coleoptera identified from the Poplar High Street site, Tower Hamlets, London. 7 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 78 records from Planktic foraminifera abundance of Hole 14-144B. 10 records from Range table from planktonic foraminifers in ODP Hole 182-1126A. 871 records from Benthic foraminiferal assemblages (dead), surface data. 220 records from Mammals in MZNA-VERT: project Loza. 1965 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 164 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE4. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 45 records from Wasser-Lernort Nettemündung. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 10577 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 520 records from Planktic foraminifera abundance of Hole 39-357. 44 records from Planktic foraminifera abundance of Hole 19-188. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 2227 records from Fundación Miguel Lillo - Colección Ornitológica. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 96 records from Birdrace-federleser-Herford. 57 records from Heidesee / Halle. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 212 records from Nanoplankton abundance at station GeoB2017-1. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 2407 records from Range table from planktonic foraminifers in ODP Hole 139-857A. 222 records from Range table from planktonic foraminifers in ODP Hole 145-887A. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 64124 records from New Zealand Fungal and Plant Disease Collection (PDD). 8717 records from CHAS Mammalogy Collection (Arctos). 147 records from NABU-Auerochsenweide. 100 records from Birdrace-The_Ringers-Friesland. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 50 records from (Table 4) Abundances of dinoflagellates in DSDP Hole 81-552A. 590 records from Planktic foraminifera assemblage in sediment core SU90-I08. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 1829 records from Inventario florístico de la Sierra de San Carlos, Tamps. 626 records from Range table from planktonic foraminifers in ODP Hole 160-969B. 20 records from Range table from planktonic foraminifers in ODP Hole 180-1115A. 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 4 records from French Grapevine Genetic Resources Center. 507 records from Hongos hyphomycetes de áreas tropicales y semitropicales del Estado de Veracruz. 3691 records from RSPB - Black-throated Diver annual records in North Scotland, 1834-2010, RSPB, SNH, NTS, SWT, RBBP, FCS, Museum Collections. 10 records from Planktic foraminifera abundance of Hole 15-154A. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-15-5. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 20626 records from BC Coastal Waterbird Survey. 71586 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 70467 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 180 records from Range table from ostracoda in ODP Hole 144-871A. 21 records from Occurrence data of Namibimydas and Nothomydas (Diptera: Asiloidea: Mydidae). 1122 records from ZFMK DORSA. 5732 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 127996 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 3 records from A new platygastrid wasp from Florida (Hymenoptera: Platygastridae).. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 277 records from Colección de Entomología - Auchenorrhyncha. 169 records from The Pteridaceae family diversity in Togo. 5 records from Schulinnenhöfe (Gelsenkirchen). 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 38331 records from Botanical Museum, Copenhagen, Mycology Herbarium. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 2 records from Nannofossil abundance of Hole 3-21A. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 4542 records from Ibaraki Nature Museum, Algae collection. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 6 records from Wiese. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 2141877 records from Biologiezentrum Linz. 5860 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 294 records from Naturgarten Langenholtensen. 172 records from Foraminifera abundance of Hole 59-448A. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 8305 records from Collection Bryozoa SMF. 12697 records from MVZ Egg and Nest Collection (Arctos). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 35345 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 8547 records from Individual Sightings. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 70416 records from National Bat Database of Ireland. 13 records from FND "Weißer Berg" Leißling. 1 records from Waldtag in und um Seelingstädt. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 126 records from Total foraminifera counts from M35/1_MSN1050. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 209 records from Relative abundance of coccosphere-units at site GIK23414. 451 records from Nannofossil abundance of Hole 15-148. 21 records from Nannofossil abundance of Hole 6-55. 3 records from Nannofossil abundance of Hole 94-609A. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 8780 records from Artròpodes d'Andorra. 17618 records from BioGIS - Mammals - INPA database. 71 records from (Data S1) Palynology of ODP Site 113-696. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 39424 records from Irish vascular plant data 1999-2009. 148 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 15389 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 5128 records from Spider Mites Collection of Jean Gutierrez. 11 records from Zoobenthos in surface sediments off Cape Lucul. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 66709 records from United States National Plant Germplasm System Collection. 16 records from Coccolith counts of multinet M32/5_MSN986. 3 records from Nannofossil abundance of Hole 31-301. 1130 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 2182 records from Ibaraki Nature Museum, Mollusk collection. 99035 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 9421 records from The Orchid Atlas of Western Australia. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 14165 records from Entomology at ZMUC, Natural History Musem of Denmark. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 13003 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 36506 records from Plant Specimens of Kurashiki Museum of Natural History. 73 records from Phytoplankton abundance at several stations in January 2005, Chipana, Chile. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 274 records from Foraminifera abundance of sediment core BM1958.631. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 68 records from Planktic foraminifera abundance of Hole 22-213. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 646 records from Engraulidae-Clupeidae. Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas. 19 records from Occurrence of mammalia relicts at site Gröbern. 164 records from Planktic foraminifera abundance of Hole 22-215. 126 records from Planktic foraminifera abundance of Hole 32-305. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 2068 records from Dinoflagellate cyst countings of sediment core MD95-2002. 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 3 records from Analyses of the recent components of sediment core PS1215-2. 12832 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 10 records from Microzooplankton abundance and biomass at station NBP97-08-02-10. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 26 records from Planktic foraminifera abundance of Hole 20-200A. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 3 records from Microfossil abundance of Hole 50-415. 268876 records from Fiji Terrestrial Arthropods. 145 records from Whale log - observations from ANARE voyages. 62487 records from Ornitho.eus. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 17 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 105 records from BIRDRACE coesfelder_vogelkundler. 73 records from VFD-HH/SH: Pferdweide Lammert. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 2 records from Abundance of benthos infauna at station GIK23025-2. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 101 records from MVZ Mammal Observations (Arctos). 3204 records from Faunal Inventory of Morysin Nature Reserve. 251760 records from Moths Ireland. 875 records from Fish monitoring data in Lake Kasumigaura. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 117 records from Wassermann. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 176729 records from CAS Entomology (ENT). 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 61 records from Fürstenberger Ralley Teil 3. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 22 records from Phytoplankton abundance at bottle station GOM6/1. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 18 records from Meiofauna abundance in sediment core 13368-015. 308 records from Planktic foraminifera counts of sediment core V19-178. 910 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 257 records from Kernberge und Umgebung (Jena). 83 records from Planktic foraminifera abundance of Hole 14-135. 2357 records from Foraminifera abundance of Hole 17-167. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 18038 records from Sponges of Rathlin Island. 70 records from Exotic terrestrial flatworms, Macquarie Island. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 19017 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 46 records from An der Ohm, (Wettsaasen). 1351 records from Neogene palynomorpha from site 93-603, part 1. 163 records from Planktic foraminifera abundance of Hole 32-313. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 87 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 14637 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 216125 records from R. L. McGregor Herbarium Vascular Plants Collection. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 83 records from Total foraminifera counts from M35/1_MSN1043. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 14473 records from Ontario Breeding Bird Atlas 1981-1985. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 44 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 2997 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 30 records from Benthic foraminifera abundance of Hole 42-379A. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 20 records from Mikroorganismen. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 9402 records from MEXU/Plantas Vasculares. 1114 records from MEXU/Tipos de plantas vasculares. 82641 records from Vascular Plants, Observations, Oslo (O). 29 records from Klimaoasen in Köln. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 28 records from Occurrence of mammalia relicts at site Climauti II. 1 records from Planktic foraminifera abundance of Hole 8-72. 525 records from Planktic foraminifera abundance of Hole 94-609. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 1115906 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 1545 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 212169 records from MVZ Mammal Collection (Arctos). 16695 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 5139 records from Herp Collection. 3 records from Collection Xiphosura SMF. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 271 records from Planktic foraminifera counts of sediment core RC11-147. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 116639 records from The digitization of plant specimens of NTU. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 101 records from Birdrace-Herford-Birder-Herford. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 939 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 114 records from BIRDRACE VIE will rock you!. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 22 records from Nannofossil abundance of Hole 9-83A. 16 records from Occurrence of mammalia relicts at site Groß-Rohrheim. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 158052 records from Field Museum of Natural History (Zoology) Mammal Collection. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 15 records from AKG-Bensheim. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 35 records from Gym Freyung. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 102 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 748 records from Moluscos Marinhos de Augusto Nobre. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 61 records from Plant specimens of Hokkaido University Museum. 388 records from Mooswald (Freiburg). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 66 records from Foraminifera abundance of Hole 55-432A. 53 records from Planktic foraminifera abundance of Hole 29-281A. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 1 records from Results of palynological analysis of Hole 302-M0004C. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 12689 records from Mycology Herbarium, Trondheim (TRH). 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 5241 records from Nordic Genetic Resources. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 1056 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 1404 records from Arachnologie - SMNG. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 3191 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 97 records from LauWi. 48 records from Wahner Heide LK 12 Biologie. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 77 records from Benthic foraminifera abundance of Hole 84-567. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 72 records from Faunal assemblage of sediment core TR149-35. 2233 records from Chrysomelidae of Poland. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 22 records from Sediment properties of core PLG95B_06BOXG. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 5733 records from Small Mammal Research Database. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 47 records from Schulgelände Ceciliengymnasium. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 33 records from Waldstück am Schullandheim Bad Bederkesa. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 2 records from Kirchenforst. 1723 records from KTU Pinophyta. 56 records from Nannofossil abundance of Hole 94-607. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 1183 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 10454 records from The Erysiphales Collection at the Botanische Staatssammlung München. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 145180 records from Bernice P. Bishop Museum. 827 records from ZFMK Sound Archive. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 64 records from Feuchtbiotop Weidenkaule. 30 records from Nannofossil abundance of Hole 8-71. 115 records from Nannofossil abundance of Hole 29-279A. 9 records from Nannofossil abundance of Hole 60-455. 21 records from Nannofossil abundance of Hole 24-232A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 7070275 records from Great Backyard Bird Count. 61226 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 12026 records from Arizona State University Amphibian and Reptile Collection. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 12 records from Ficha de Sonora aemula. 3761 records from Mountain Invasion Research Network (MIREN) survey. 90 records from Schulhof Bühlschule Giengen. 131 records from Unser Schulhof - eine Apotheke. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 302 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 353 records from Colección de Entomología - Arthropoda. 35266 records from Kathryn Kalmbach Herbarium. 84521 records from BioGIS - Vascular plants - INPA database. 103 records from BIRDRACE Die Otzberger. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 70 records from Parkuntersuchung Weißer See. 315 records from Planktic foraminifera counts of sediment core RC17-69. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 4826 records from Vascular Plants Collection of National Museum of Nature and Science. 13750 records from Impetus - Herbarium Hamburgense. 6 records from Sediment properties of core PLG93_BCORE1. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 5 records from Analyses of the recent components of sediment core PS1400-4. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 2022 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 406 records from Harpactus Shuckard. 48 records from Freiheitsring (Frechen). 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 241 records from Planktic foraminifera abundance of Hole 67-499B. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 23 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 8 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 10648 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 2189 records from Algae, Specimens, Agder naturmuseum (KMN). 340951 records from Entomology, Natural History Museum, University of Oslo. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 84 records from BIRDRACE Birding for Nature. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 19 records from Nannofossil abundance of Hole 31-298. 76 records from Coccoliths in sediment core PS1533-3. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 778 records from Planktic foraminifera abundance of Hole 40-362. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 57 records from Nannofossil abundance in sediment core PS1311-4. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 168 records from Weidenhüttendorf an der Würm (München). 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 10482 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 12 records from Abundance of radiolaria at station LV28-40-2. 94 records from Coccolith counts of multinet SO119_MSN1298. 6 records from Nannofossil abundance of Hole 7-63. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 672 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 42 records from Foraminifera abundance of Hole 24-236. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 1028826 records from SEAMAP - marine mammals, birds and turtles. 32698 records from Fish tag database. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 2937 records from Homoptera. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1200 records from monocotyledonous_geophytes_of_fergana_valley. 529 records from Collection Crustacea - KAUMM. 40 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 36301 records from Pelagic Fish Observations 1968-1999. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 302 records from Stadtpark Sulzbach-Rosenberg. 1 records from Planktic foraminifera abundance of Hole 54-420A. 310 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 235 records from Total foraminifera counts from multinet M31/3_MSN905. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 181 records from Collection Crustacea ZMG. 86 records from Fliegenhaupt Marksuhl. 1130 records from Ostracoda in sediment core PS51/154-11. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 869 records from Lepidoptera Observations from New Zealand by Donald Hobern. 99 records from Planktic foraminifera abundance of Hole 94-610E. 1 records from Pollen and spore abundance of Hole 42-379A. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 145 records from privater Garten. 774 records from Planktic foraminifera abundance of Hole 80-549A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 7 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 6056 records from Lichens of Knyszyn Forest. 1582352 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 184156 records from The Flora of County Waterford. 74 records from SuLaMa reptile monitoring. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 24. 588 records from Relative abundance of ostracods in sediment core Lz1120. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 107 records from BIRDRACE Herford Birders. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 2 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1 records from Hausgarten. 10269 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 441 records from Pollen analysis of surface samples from Germany and Austria. 16307 records from West African Vegetation Database. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 24402 records from Ibaraki Nature Museum, Arthropoda collection. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 175 records from INSECT COLLECTION. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 320 records from Myxomycetes collection of the University of Eastern Finland. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 93 records from Südwestlich der Parkwiesen. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 107 records from Planktic foraminifera abundance of Hole 18-180. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 30890 records from MEXU/Asteraceae. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 3 records from CNIN/Mantodea. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 25 records from Benthic foraminifera abundance of Hole 1-4. 2 records from Benthic foraminifera abundance of Hole 42-376. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 3481 records from Irish National Frog Database. 2839 records from Rocky Shore Macroalgae. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 256 records from BIRDRACE Upupa epöpse. 20 records from Biological Records Centre - RISC Non-Native Species Records for Rhododendron Leafhopper. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 6 records from UWYMV Herpetology Collection (Arctos). 201 records from Mammals in MZNA-VERT: project CAS. 10883 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2846 records from Coleoptera, NEF. 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 77 records from Total foraminifera counts from M35/1_MSN1075. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 177 records from Donauinsel des BN bei Entau. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 9721 records from Birds of Ireland. 91 records from Benthic foraminifera abundance of Hole 84-569A. 53 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 88 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 1392 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 454 records from Collection des Mollusques (BOUM). 18 records from Landschaftsschutzgebiet Buchhorst2. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 347 records from (Table 4) Standing stock values of important species in surface sediments. 49180 records from Environment Agency - Environment Agency Non-native Species records v1. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 11626 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean (OBIS South America, SOUTHERN OCEAN SUB-NODE). 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 12 records from Abundance of radiolaria at station LV28-44-1. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 356 records from Biotope in Rheine - Aktion 350. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 144 records from BIRDRACE Punkbirder Helgoland. 3 records from Antarctic Arrow worms. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 1554 records from Biodiversidad de Datura (Solanaceae) en México. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 5 records from Memorial University Botanical Garden Collection. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 6 records from Nannofossil abundance of Hole 55-430B. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 52 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 8 records from Pollen and spore abundance of Hole 42-380. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 6987 records from National Trust - Ickworth species data held by The National Trust.. 690 records from Mid Ulster Hare Surveys 2012-2015. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 114 records from BIRDRACE Di-Bi-Di-Birder. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 9614 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 679 records from Results of palynological analysis of Hole 302-M0004A. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 87 records from Klütwald. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 279 records from Planktic foraminifera abundance of Hole 11-98. 777 records from Flora acuática de Querétaro. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 76 records from Colección de Entomopatógenos de México (CNRCB). 107 records from 1st Austrian Birdrace (Wien). 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 44 records from Flora und Fauna in unserer Kita. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 2619 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 13639 records from Senckenberg - CeDAMar Resource. 49 records from Collection Thysanoptera SMF. 7795 records from Hymenoptera collection, Natural History Museum, University of Oslo. 492 records from Verneplan Hjerkinn karplanter. 53606 records from BioMar - LIFE project. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 49637 records from Monitoring data from the federal state Hesse (Germany). 13624 records from Mammal collection, Natural History Museum, University of Oslo. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 45 records from Nannofossil abundance of Hole 28-265. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 4 records from Estimated plankton abundance at station PS63/064-6. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 57 records from Occurrence of mammalia relicts at site Moladova V. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 117 records from Muskox Abundance. 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 6660 records from Weevils of the Tatra Mts.. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 27 records from Coleção de Nemertea do Museu Nacional - UFRJ. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 5 records from Streuobstwiese (Mittelgasse 4). 153 records from Selztal bei Friesenheim. 214 records from Binsenwiesen. 57 records from Garten in Schmölln. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 33 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 194 records from Collection Cnidaria - ZMB. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 2088 records from Benthic foraminifera of sediment core MD99-2286. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 120714 records from Arizona State University Lichen Collection. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 21 records from Meiofauna abundance in sediment core 13077-006. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 180 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 38984 records from Herbarium (UNA). 718 records from Zukünftiges NSG Höftland/Bockholmwik. 1042 records from Planktic foraminifera abundance of Hole 37-333. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 231 records from Gunma Museum of Natural History, Fish Specimen. 493140 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 132 records from Insect (HUNM-IN). 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 13329 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 1 records from Planktic foraminifera abundance of Hole 8-73. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 246 records from Benthic foraminifera abundance of Hole 73-524. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 764 records from BioGIS - Fish - INPA database. 36384 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 4 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 118488 records from Mycology herbarium, Oslo (O). 194 records from Colección Herpetológica de la Patagonia. 133081 records from NINA insect database. 2539 records from Inventory of Antarctic seabird breeding sites. 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 763 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 103322 records from Invertebrates Collection of the Swedish Museum of Natural History. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 86 records from Pollen analysis of sediment core GIK16856-2. 122 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2 records from Echinodermata ZMK. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 269 records from 3. Tag der Artenvielfalt Hockenheim. 28498 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 8 records from Krittenhorster Wald (Ostkilver). 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 145 records from Phytoplankton abundance at station CD46_0405C#7. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 921 records from Planktic foraminifera counts of sediment core RC14-37. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 9572 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 12 records from Lepidoptera specimen database of Japan. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 23879 records from svalbardflora.net. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 1267 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 304538 records from Observational database of Icelandic plants. 10930 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 2 records from Nannofossil abundance of Hole 6-49. 2032 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 113 records from Collection Hydrozoa - ZMB. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 296 records from DJH. 141 records from Schulhof und Anlagensee in Nellingen. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 83 records from North Carolina State Museum of Natural Sciences Fishes Collection. 588 records from NHT flora. 16564 records from UPCB - Herbário do Departamento de Botânica. 1 records from Diatom abundance of Hole 95-613. 32 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 134 records from Myriapoda - SMF. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 4191 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 31379 records from MSB Bird Collection (Arctos). 767 records from BioGIS - Bats - Asaf Tsoar database. 78799 records from natagora-earlybirds. 54501 records from Fish Specimens. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 35 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components of sediment core PS1215-2. 692 records from Planktic foraminifera abundance of Hole 40-360. 94 records from Planktic foraminifera abundance of Hole 80-550. 70 records from Planktic foraminifera abundance of Hole 84-569A. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 99 records from Düne am Ulvenberg (Darmstadt). 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 961 records from Spencer Entomological Museum. 2148 records from Eppingen und Umgebung. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 76 records from Occurrence of mammalia relicts at site Vindija. 6 records from Planktic foraminifera abundance of Hole 23-226. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 11 records from Observation of birds at station PS14/156 along 49° West. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 146019 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 820426 records from Fauna Atlas N.T.. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 163 records from Tiere und Pflanzen am Pfannenbach. 30 records from Leben auf einer Sturmfläche. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 498 records from Dinoflagellate abundance of Hole 94-611C. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 50 records from Lindesnes. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 278 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 4 records from Nannofossil abundance of Hole 29-281A. 32112 records from SBMNH Vertebrate Zoology. 316 records from Planktic foraminifera counts of sediment core V14-101. 12697 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 347639 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 1 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 4004 records from Sightings Map of Invasive Plants in Portugal. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 27 records from Zwickau- Schwanenteich. 87 records from Total foraminifera counts of trap L2_92_B49. 11 records from Nannofossil abundance of Hole 6-56B. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 73 records from Planktic foraminifera abundance of Hole 2-11. 18 records from Planktic foraminifera abundance of Hole 32-310. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1 records from Abundance of benthos infauna at station GIK23004-3. 48913 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 2991 records from Millenium Seedbank (MSB). 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 23215 records from rmca-albertine-rift-butterflies. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 5 records from Tuttlinger Tag der Artenvielfalt. 14 records from Nannofossil abundance of Hole 85-573. 28 records from Nannofossil abundance of Hole 26-253. 18 records from Meiofauna abundance in sediment core 13200-012. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 497 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 5862 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 759 records from Planktic foraminifera abundance of Hole 47-398D. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 4139 records from Marie-Victorin Herbarium (MT) - Bryophytes. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 92 records from Siliceous microfossil occurrence, Site 177-1094. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 264743 records from ArtenFinder. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 84 records from BIRDRACE Vogelscheuchen. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 2 records from Nannofossil abundance of Hole 74-526. 104 records from Ross Sea Pycnogonids. 8981 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 131 records from Artenvielfalt auf dem Schulgelände. 8 records from Occurrence of mammalia relicts at site Wretton. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 139 records from Siliceous microfossil occurrence, Site 177-1093. 21312 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 5327 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 878 records from Planktic foraminifera abundance of Hole 84-568. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 405 records from Collection Graptolithina fossil SMF. 56741 records from Insect Collection of Taiwan Forestry Research Institute. 7 records from Additions to the myxobiota of the Åland Islands. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 379 records from UAM Herpetology Collection (Arctos). 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 17 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 24 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 86088 records from NINA Vanndata øvrige arter. 20 records from Motzener Tonsee. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 244 records from WildesMoor bei Schwabstedt. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 44 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 21146 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 772 records from Fishes of the Congo River 2010 Expedition. 1436 records from Cowan Tetrapod Collection - Herpetology. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 374561 records from University of Florida Vertebrate Paleontology. 310 records from Lepidoptera collection, NTNU, Trondheim. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 26 records from Ostracoda abundance of Hole 13-132. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 52865 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 52 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 281250 records from Quadrige. 25545 records from Formidabel; Belgian Ants Database. 37 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 16 records from Dinoflagellate cysts of surface sediments. 96 records from BIRDRACE OAG Neuwerk. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 3 records from Nannofossil abundance of Hole 51-417D. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 76911 records from University of British Columbia Herbarium (UBC) - Algae Collection. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 43638 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 64 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 237 records from RSPB - Capercaillie national surveys (SCARABBS). 29644 records from Phanerogamic Botanical Collections (S). 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 45 records from Parcela Permanente en el Pantano Martos. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 8 records from Abundance of radiolaria at station LV28-29-1. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 150216 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 9948 records from Bees of Canada / Gschwendtner property collection. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 2 records from Smear slide analysis of sediment core GeoB7427-2. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 14997 records from iziko South African Museum - Fish Collection (AfrOBIS). 556 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 1589 records from Global caridean shrimp fauna. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 6 records from Ökosysteme rund um Wedel. 19515 records from MfN - Fossil invertebrates Ia. 16 records from Nannofossil abundance of Hole 47-398B. 66 records from Range table from ostracoda in ODP Hole 151-910D. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 102 records from Ostracod abundance in sediment core Lz1120. 23077 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 155 records from Bergbaufolgelandschaft am Muldestausee. 741 records from Planktic foraminifera abundance of Hole 20-200. 84943 records from Herbarium of Umeå University (UME). 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 54 records from Wiese am Unterbecken. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1443 records from Odonata of the Congo River 2010 expedition. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 1 records from Boraginaceae (Cynoglossum cherangauiense). 112 records from Total foraminifera counts of multinet M11/1_MSN526. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 349 records from Planktic foraminifera counts of sediment core V20-170. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 21447 records from Herbarium de Geo. B. Hinton, México. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1627 records from The Irish Squirrel Survey 2007. 67 records from Tongrube bei Hettstedt. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 777 records from Planktic foraminifera counts of sediment core RC17-108. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 535 records from Benthic foraminifera abundance of Hole 73-522. 455 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 27 records from Benthic foraminifera abundance of Hole 34-320A. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 16040 records from Naturalis Biodiversity Center (NL) - Porifera. 1983 records from Seabird 2000. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 4 records from Collection Pantopoda SMF. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 241 records from BIRDRACE RennVögel Münsterland. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 236 records from GENT Lactarius Deliciosi. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5640 records from UPRM Invertebrate Collection. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 9088 records from Flora of Słowiński National Park, Poland. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 8407 records from NYSM Birds. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 112 records from BIRDRACE Gütersloher Gimpel. 2633 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 48 records from Diatom assamblage in samples from sediment trap OG5. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 57 records from Schulgarten Janusz-Korczak-Realschule. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 348999 records from BSBI tetrad data for Ireland. 4094 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 102 records from Benthic foraminifera abundance of Hole 42-372. 1 records from Abundance of benthos infauna at station GIK23062-2. 10902 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 7685 records from European riparian ground beetles. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1 records from Antarctic Marine Amoebae. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 70615 records from Marsh Monitoring Program - Birds. 11370 records from Distribution of planktic foraminifers of core V22-174. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 24 records from Occurrence of mammalia relicts at site Overmere. 15 records from Herdengelhoehle taxa and datings. 2083 records from Planktic foraminifera abundance of Hole 72-517. 19 records from Dinoflagellate abundance of Hole 81-553A. 1 records from Microfossil abundance of Hole 42-378. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 1525 records from The French Collection of Medicago truncatula. 428 records from EAN - Herbário Jaime Coelho de Moraes. 19 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 16 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 1 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1997 records from Aves de la cuenca media del río Bogotá. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 97 records from Döchtbühlwald (Bad Waldsee). 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 140273 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 91 records from BIRDRACE SchrägeVögel. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 703809 records from Australian National Herbarium (CANB). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 6 records from Nannofossil abundance of Hole 6-49. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 7501 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 396 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 76 records from Faunal assemblage of sediment core GS7603-10. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 35 records from Nannofossil abundance of Hole 78-543. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 7 records from Nannofossil abundance of Hole 38-336. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 11964 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 82736 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 1298 records from Planktic foraminifera abundance of Hole 23-219. 38 records from Microfossil abundance of Hole 21-206C. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 36 records from Nannofossil abundance of Hole 14-141. 596 records from Planktic foraminifera counts of sediment core A15-558. 753 records from Planktic foraminifera counts of sediment core V28-127. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 1023 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 1046 records from NBM Insects. 169 records from Planktic foraminifera counts at CTD station PS55/051. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 2020 records from Bryophyte collection of Jyväskylä University Museum. 8627 records from CRI - Herbário Pe. Dr. Raulino Reitz. 75961 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 9 records from Nannofossil abundance of Hole 1-2. 591 records from Planktic foraminifera counts of sediment core V16-25. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 19 records from Microplankton data off Mejillones, 2006, Chile. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 84 records from Benthic foraminifera abundance of Hole 84-566C. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 1 records from Dinoflagellate abundance of Hole 19-183. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 65 records from BIRDRACE Federal Birds of Investigation FBI. 248 records from Schulgarten der Volksschule. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 477 records from EASIANET. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 9542 records from Countryside Council for Wales - UK Biodiversity Action Plan Invertebrate Data for Wales. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 1101 records from Relative abundance of ostracods in sediment core Co1202. 143 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 371 records from Planktic foraminifera abundance of Hole 63-470. 162042 records from KU Museum of Invertebrate Paleontology. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 10075 records from Nematoda of Costa Rica (INBio). 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 75985 records from Irish Vascular Plant Data - Paul Green. 18703 records from Endemic plants of the Congo basin. 65554 records from CAS Ornithology (ORN). 46685 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 8 records from Nannofossil abundance of Hole 49-409. 260 records from Range table from ostracoda in ODP Hole 144-873B. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 201 records from BioAcoustica: Wildlife Sounds Database. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 8100 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 85 records from Birdrace-Die_Paradiesvögel-Herford. 95 records from Vielfalt verschiedener Wiesen. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 44 records from Wiesen am Treffpunkt Freizeit. 173678 records from Mammalogy Collection - Royal Ontario Museum. 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 39 records from Red list project inventory, fungi. 12 records from Kindergarten. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 17 records from Hazel Dormouse in Ireland. 43 records from Schulgelände Thurmair-Gymnasium. 3 records from Blankenfelder See. 504 records from Schatzinsel Wangerooge. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 16075 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 59 records from Schulgelände SGD/Viersen. 33 records from Schüler erforschen die Helme-Aue. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 1406 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 239 records from Naturerlebnisraum Koppelsberg. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 5 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 16 records from Nannofossil abundance of Hole 9-77B. 129 records from Nannofossil abundance of Hole 29-284. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 12 records from Nannofossil abundance of Hole 20-200. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 85422 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 68077 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 495 records from Life Science National Tsing Hua University. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 8523 records from Distribution of planktic foraminifers of core RC24-16. 7 records from Analyses of the recent components of sediment core PS1219-1. 50 records from Planktic foraminifera abundance of Hole 60-457. 6 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 262 records from Speothos Venaticus por Guillermo Gil. 19756 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 4175 records from Badger and Habitats Survey of Ireland. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 15 records from Occurrence of mammalia relicts at site Dendermonde. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 1346 records from Weevils of Poland. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 783 records from Phytoplankton abundance in surface water during cruise CD61. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 5 records from Schulwald Regionale Schule Sprendlingen. 14941 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 59304 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 3 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 178408 records from Essig Museum of Entomology. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 186 records from Planktic foraminifera abundance of Hole 94-610. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 21 records from Collection Ctenophora SMF. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4728 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 752516 records from Museum of Comparative Zoology, Harvard University. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 24050 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 233 records from Föhrenried (Fronreute und Baindt). 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 7 records from Nannofossil abundance of Hole 5-33. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 4710 records from Lyman Entomological Museum. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 316 records from Planktic foraminifera counts of sediment core RC11-86. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 6666 records from Observaciones de Especies Silvestres (by Charif Tala). 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 14 records from Nannofossil abundance of Hole 8-72A. 3 records from Nannofossil abundance of Hole 22-212. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 9 records from Coccolith counts of multinet M32/5_MSN982. 7 records from Nannofossil abundance of Hole 9-82A. 15 records from Microfossil abundance of Hole 59-450. 4 records from Nannofossil abundance of Hole 52-418. 6493 records from UWBM Herpetology Collection (Arctos). 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 249 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 353 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 14602 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 354 records from Foraminifera distribution of sediment core KS310. 164 records from Planktic foraminifera abundance of Hole 94-610B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 13 records from Nannofossil abundance of Hole 94-607A. 5 records from Nannofossil abundance of Hole 84-569. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 593 records from Ostracoda in sediment core PS51/159-10. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 76 records from The Ants of Bulgaria. 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 56 records from Estetal (Buxtehude). 15 records from Kühnauer Aue und Kühnauer See. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 896 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 576 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 1254 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 157035 records from The Himalayan Uplands Plant database (HUP Version 1). 351 records from Great Lakes Forestry Centre Insect Collection. 41 records from Altholzparzelle Eilenriede Hannover. 125 records from Artenbestimmung. 94 records from Planktic foraminifera abundance of Hole 32-310. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 19 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 176153 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 34 records from Order Araneae. 308 records from Wangerooge. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 2069 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1249 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 40550 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 14693 records from The Gordon Alexander Orthoptera Collection. 3 records from Planktic foraminifera abundance of Hole 54-424B. 325 records from Planktic foraminifera abundance of Hole 32-305. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 149 records from Bayerische Donau - Neu Ulm. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 32468 records from MedOBIS (EurOBIS). 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 80 records from BB-Biodiversität b. 317 records from Planktic foraminifera counts of sediment core RC14-29. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 12 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 4256 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 233 records from Total foraminifera counts from M35/1_MSN1044. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 32 records from Nannofossil abundance of Hole 67-499. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 703 records from Planktic foraminifera counts of sediment core V25-59. 35 records from Ortsrand Zandershagen. 45 records from Antarctic Isopods. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 5 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 161910 records from UA Herbarium. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 180 records from Paul-Gerhardt-Schule Dassel. 28 records from Stadtpark Prinzengarten (Sigmaringen). 135 records from Waldi-Weiher. 612 records from INRA-Versailles Arabidopsis natural variants. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 5238 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 238 records from Coccoliths in ODP Hole 104-643A. 3 records from Nannofossil abundance of Hole 9-80. 2 records from Nannofossil abundance of Hole 29-280A. 16 records from Abundance of radiolaria at station LV28-3-3. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 2182 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 40 records from Tiere und Pflanzen um uns herum !. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 353 records from Stadtgebiet (Dannenberg). 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 60 records from Planktic foraminifera abundance of Hole 19-192. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1015 records from Irish Marine Turtle Database. 19121 records from Biological Records Centre - Cerambycidae Dataset. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 1474 records from Herbarium Rhoenmuseum Fladungen. 89 records from Birdrace-Team_Wangerooge-Friesland. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 3633 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 4974 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 85 records from Sedimentological investigation on core V25-45. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 904 records from JOIw - Xiloteca Joinvillea. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 100 records from Grenzturm Hohen Neuendorf. 5 records from Fledermäuse u. nachtaktive Insekten. 269 records from BIRDRACE Dithmarscher Deichhühner. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 122 records from Phytoplankton abundance at station CD46_1005C#4. 482 records from Kühmark bei Wetzlar. 185 records from Abundance of coccosphere-units of site GIK23414. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 10116 records from CUMV Mammal Collection (Arctos). 35832 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 102 records from Birdrace-OAG_Neuwerk-Hamburg. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 2 records from Nannofossil abundance of Hole 7-64A. 31 records from Nannofossil abundance of Hole 4-23. 47 records from Lepidurus arcticus survey Northeast Greenland 2013. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 23 records from Landwehrbach. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 531415 records from Swiss National Butterflies Databank. 1377 records from Red list project inventory, lichens. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 10 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 691 records from RSPB - Black grouse national surveys (SCARABBS). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 181 records from Alien Species in Poland - Animals. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 1128 records from Southern Ocean Ostracoda (except Halocypridina). 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 7811 records from Institut Botanic de Barcelona, BC-Histórico. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 29917 records from Natural History Museum, University of Tartu. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 34 records from Aschelminth collection of National Museum of Nature and Science. 43 records from Collection Tardigrada SMF. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 2644 records from Invertebrates compiled by W.Block. 58 records from Lüner Holz (Lüneburg). 203 records from Planktic foraminifera abundance of Hole 72-515B. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 48 records from Benthic foraminifera abundance of Hole 42-380A. 892 records from Weevils of Wales and England. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 92 records from Nottekanal, Klasse 7 - 10. 525 records from Benthic foraminifera abundance of Hole 40-360. 8 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 13345 records from CUMV Fish Collection (Arctos). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 1 records from Abundance of benthos infauna at station GIK23013-2. 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 7034 records from Mollusca collection of National Museum of Nature and Science. 12 records from Art´n Vielfalt im Kinderwald. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 483 records from Artenvielfalt im Rhein-Neckar-Raum. 69 records from Mönchspark. 20 records from Nannofossil abundance of Hole 7-63A. 31 records from Bayerische Donau - Tapfheim. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15926 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 5955 records from HRCB - Herbário Rioclarense. 3237 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 567 records from Collection of Hymenoptera. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 7551382 records from BirdLife Australia, Birdata. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 92 records from Nannofossil abundance of Hole 31-296. 90 records from Planktic foraminifera counts of sediment core RC13-158. 63 records from Planktic foraminifera counts of sediment core V19-21. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 137 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 7470 records from National Taiwan University. 60 records from Schafsweide Seniorenhaus Berghof. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 61 records from BIRDRACE Baumläufer. 198 records from Total foraminifera counts from M35/1_MSN1047. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 4 records from Nannofossil abundance of Hole 16-156. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 7 records from Nannofossil abundance of Hole 27-259. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 704 records from Planktic foraminifera counts of sediment core V18-207. 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 429 records from Larval fish at Helgoland Roads in 2004. 76 records from BIRDRACE Nachtigallen. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 1294 records from MfN - Fossil vertebrates III. 14 records from Nannofossil abundance of Hole 14-140. 4 records from Range table from nannofossils in ODP Hole 139-857A. 2 records from Chaetognatha - SMF. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 20 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 57 records from Schulgarten Fichteschule. 54 records from Biotope im Schulumfeld. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 7924 records from Dinoflagellate cysts in surface sediments. 39 records from Calcareous dinocysts along profile Ruegen. 18 records from Smear slide analysis on sediment core GeoB4206-1. 29 records from Naturerfahrung. 27 records from Pollen data of trap CB3. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 146 records from LK 11 im Mönchspark. 104 records from BIRDRACE Andechser Stativträger. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 2321 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 191 records from Foraminifera abundance of sediment core C1960.202. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 106 records from Arteninventar rund um den Rannahof. 152 records from Plasm bearing foraminifera counts of multinet SO118_MSN1252. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 5 records from Analyses of the recent components of sediment core PS1216-1. 4914 records from UCM Bird Collection (Arctos). 1 records from Occurrence of mammalia relicts at site Ejstrup. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 10 records from Oberservation of birds at station PS14/143 along 49° West. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 786 records from Planktic foraminifera abundance of Hole 72-518. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 1641 records from Arácnidos de Centroamérica. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5115-1. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 873 records from Kartlegging av spredning av fremmede bartrær. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 15 records from Urwald 2 (Bad Waldsee). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 232 records from Distribution of planktic foraminifera of sediment trap OG5. 22 records from Phytoplankton abundance at bottle station GOM1/6. 171 records from Sahrbachtal Kreis Ahrweiler. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 89 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 751 records from Planktic foraminifera abundance of Hole 49-408. 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 6 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 217 records from Nanoplankton abundance at station GeoB2012-2. 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 56 records from Zitadelle Berlin-Spandau (7b). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 59 records from Schulteich Freie Waldorfschule Darmstadt. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 111545 records from Highland Biological Recording Group - HBRG Insects Dataset. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 264 records from Planktic foraminifera counts of sediment core RC12-339. 137 records from Planktic foraminifera counts of sediment core V28-25. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 19 records from Pollen record from Mamontovy Klyk. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 327 records from Foraminifera abundance of Hole 58-443. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 23 records from Benthic foraminifera abundance of Hole 93-603. 1763 records from Arachnida of Costa Rica (INBio). 49 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 16666 records from UFP - Herbário UFP - Geraldo Mariz. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 153 records from annex1. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 3175 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 465 records from Philosophenwald und Wieseckaue in Gießen. 79 records from Umgebung von Schorndorf. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 15714 records from imr_mareano_beamtrawl. 7 records from Nannofossil abundance of Hole 24-233A. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 12 records from Nannofossil abundance of Hole 74-528A. 4 records from Nannofossil abundance of Hole 55-430A. 2 records from Nannofossil abundance of Hole 18-174A. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 23 records from AlgaTerraMovies. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 376 records from Wupperaue bei Kemna (Wuppertal). 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 1059 records from Planktic foraminifera abundance of Hole 15-148. 13 records from Foraminifera abundance of Hole 57-438B. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 3 records from Dinoflagellate abundance of Hole 85-572. 3093 records from Biological Records Centre - Mosquito Recording Scheme. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 78 records from Planktic foraminifera counts of sediment core A180-73. 3382 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 65079 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 422 records from Antarctic Krill Euphausia superba. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 239 records from Point Pelee National Park Collection, Canada. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 16 records from MVZ Herp Observations (Arctos). 1658 records from MISE Project Waterford Otter Records, 2011-2015. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 84 records from BIRDRACE Avinauten. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 3489 records from Polish seed gene bank – historical passport data of accessions. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 4 records from Zwischen Enz und Schule. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 521 records from Bayerische Donau - Leipheim. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 1972 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 2694 records from Recuento de la diversidad florística de Veracruz. 2733 records from Anfibios y reptiles del estado de Querétaro. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 41915 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 221 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 7341 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 1017 records from Planktic foraminifera abundance of Hole 26-253. 3763 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1571 records from Diptera, NEF. 2211 records from JOI - Herbário Joinvillea. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 63 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 751608 records from Paleobiology Database. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 2 records from Nannofossil abundance of Hole 10-87. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 6113 records from Hongos del estado de Veracruz. 661 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 16232 records from Birds Specimens. 475 records from Herp specimens. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 73 records from Tiergarten (Zeitz). 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 1 records from Occurrence of mammalia relicts at site Egtved. 3 records from Planktic foraminifera abundance of Hole 54-419. 59 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 134 records from Birdrace-Easy_Birders-Plön. 17 records from Coccoliths in sediment core PS1527-2. 8064 records from Vascular Plants Collection of Sagamihara City Museum. 321 records from Fuldaaue (Stadtgebiet Fulda). 1742 records from Eggs Specimen. 3669 records from ARKO strandeng. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 221 records from Foraminifera abundance of sediment core IN68-5. 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 3939 records from Census of plant species in Pahou forest reserve. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 6 records from Fließgewässeruntersuchung am Haselbach. 679 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 347 records from Planktic foraminifera abundance of Hole 21-209. 500 records from Foraminifera abundance of Hole 48-404. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 765 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 778 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species: Great crested newts. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 12 records from Meiofauna abundance in sediment core 13200-046. 284699 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 133 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 3786 records from Faun. 107 records from Hypogean Crustacea of Ireland. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 3330 records from Collection botanique Le Grand A. (BOUM). 103 records from Birdrace-Die_Nachtigallen-Herford. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 80 records from Total foraminifera counts of multinet M12/3_MSN543. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 88 records from Total foraminifera counts of trap L2_92_A43. 1098 records from Pinos del Noreste de México (UANL). 1120 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 94 records from Total foraminifera counts of multinet M21/4_MSN697. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 2 records from Nannofossil abundance of Hole 74-525A. 72 records from Occurrence of nannoplankton observed in Early Pliocene samples from Zanclean stratotype of Capo Rossello, Sicily (Table I). 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 142 records from Collection Crustacea NHCY. 9192 records from Herbarium of the Université Libre de Bruxelles. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_240-4. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 279 records from Koleopterologen
Keywords: GBIF; biodiversity; species occurrences